Continuation, reduction, or withdrawal of tofacitinib in patients with rheumatoid arthritis achieving sustained disease control: a multicenter, open-label, randomized controlled trial - Mengyan Wang; Yu Xue; Fang Du; Lili Ma; Liang-jing Lu; Lindi Jiang; Yi-Li Tao; Chengde Yang; Hui Shi; Honglei Liu; Xiaobing Cheng; Junna Ye; et al. (Chinese Medical Journal, 2023)
Abstract. Background:. Rheumatoid arthritis (RA), a chronic systemic autoimmune disease, is characterized by synovitis and progressive damage to the bone and cartilage of the joints, leading to disability and reduced quality of life. This study was a randomized clinical trial comparing the outcomes between withdrawal and dose reduction of tofacitinib in patients with RA who achieved sustained disease control. Methods:. The study was designed as a multicenter, open-label, randomized controlled trial. Eligible patients who were taking tofacitinib (5 mg twice daily) and had achieved sustained RA remission or low disease activity (disease activity score in 28 joints [DAS28] ≤3.2) for at least 3 months were enrolled at six centers in Shanghai, China. Patients were randomly assigned (1:1:1) to one of three treatment groups: continuation of tofacitinib (5 mg twice daily); reduction in tofacitinib dose (5 mg daily); and withdrawal of tofacitinib. Efficacy and safety were assessed up to 6 months. Results:. Overall, 122 eligible patients were enrolled, with 41 in the continuation group, 42 in the dose-reduction group, and 39 in the withdrawal group. After 6 months, the percentage of patients with a DAS28-erythrocyte sedimentation rate (ESR) of <3.2 was significantly lower in the withdrawal group than that in the reduction and continuation groups (20.5%, 64.3%, and 95.1%, respectively; P < 0.0001 for both comparisons). The average flare-free time was 5.8 months for the continuation group, 4.7 months for the dose reduction group, and 2.4 months for the withdrawal group. Conclusion:. Withdrawal of tofacitinib in patients with RA with stable disease control resulted in a rapid and significant loss of efficacy, while standard or reduced doses of tofacitinib maintained a favorable state. Trial Registration:. Chictr.org, ChiCTR2000039799.